(3TQM GdefXheI GdYeQjWjIs - (3CHhESMGb HQgGf GdOjf EHQGgje Hf MSf GdCMSGFj GdfLOjs; (3GdYeQjWj , jMji Hf fhQ GdOjf CHj GdNjQ Hf ehSi GdTGaYj GdCfUGQj GdGRgQj, TQa GdOjf,J (B989 (3g` s
(3ChdgG (B:s
(3hHYO, adeG cGf Yde GdfMh ef Hjf Ydhe GdYQHjI HGdeRjI GdYdjG cGf ef GdCge dPhj Gdgee GdYGdjI s
(3BNQgG (B:s
(3hLeGYI JHYge GdfGXe hCcKQge de jKHJg, heG PcQ ef GdCeKdI ebOQ HGddGe YfOge Ydi GdJhSY s
(3Vef eLehY s
(3hCKQ WeSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdfMhs